PENGEMBANGAN WISATA MINAT KHUSUS BERBASIS SPIRITUAL DI DESA WISATA PESAREAN GUNUNG KAWI: PENDEKATAN PARIWISATA BERKELANJUTAN - Chintya Paramita Puspita; Apri Kuntaraningsih; Okta Purnawirawan; Sataisy Nabila; Kafi Kafi (Jurnal Pariwisata Tawangmangu, 2026)
This study aims to analyze the development of spirituality-based special-interest tourism in Pesarean Gunung Kawi Tourism Village and to understand tourists' meanings and experiences within the local cultural context. The growing interest in spiritual tourism reflects a shift in tourist preferences toward more personal and reflective experiences. This study employs a qualitative approach with an ethnographic design to explore cultural practices, social interactions, and spiritual experiences at the research site. Data were collected through semi-structured interviews, participatory observation, and documentation involving tourism village managers, community leaders, local business actors, and tourists selected through purposive and snowball sampling techniques. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña through data reduction, data display, and conclusion drawing. The findings reveal three key themes: (1) spiritual tourism is understood as a practice integrating religious, cultural, and personal experiential dimensions; (2) tourists exhibit characteristics of special interest tourists, driven by intrinsic motivations such as the search for meaning, inner peace, and transformational experiences; and (3) tourism development faces challenges including visitor fluctuation, infrastructure limitations, and the risk of cultural commodification. This study contributes theoretically by integrating the concepts of special interest tourism, spiritual tourism, and sustainable tourism within an ethnographic framework.